Secretory Leukocyte Protease Inhibitor: A Potential Target to Improve Immune Response in Ovarian Cancer - Echaibi, Maryam (Université d'Ottawa | University of Ottawa, 2024)
Understanding the communication between cancer cells and immune cells is crucial, particularly in ovarian cancer, given its aggressive and heterogeneous nature. This interaction becomes even more complex when cancer cells undergo epithelial-to-mesenchymal transition (EMT), which enhances their invasive capabilities. In this study, we analyzed cell-cell communication in 34 high-grade serous ovarian cancer single-cell RNA-sequencing datasets, focusing on three distinct EMT phenotypes: epithelial, partially mesenchymal, and mesenchymal. Our findings revealed a significant interaction mediated by the Secretory Leukocyte Protease Inhibitor (SLPI), a small, secreted protein highly expressed in ovarian cancer cells, particularly in the mesenchymal state, with CD4 receptors on immune cells. The functional consequences of this interaction are not well understood. To address this, we first identified the pathways regulating SLPI expression by comparing its baseline levels in genetically defined mouse ovarian cancer cell lines to non-cancerous cell lines. SLPI expression was found to be highly variable and primarily regulated by the MEK/ERK signaling pathway. Additionally, we explored the immune functions of SLPI both in vitro and in vivo, finding that SLPI is associated with an increased presence of immune cells expressing the immune checkpoint molecules PD-1 and its ligand PD-L1, particularly in CD4+ T cells. These results suggest that SLPI should be investigated further as a potential target to improve immune response in ovarian cancer.
Keywords: SLPI; Ovarian cancer; EMT; Tumor microenvironment